THE IMPACT OF POWDERS AND OIL ADDITIVES OF CINNAMON AND CLOVE IN QUAILS DIET AS ANTISTRESSOR AND ANTIOXIDANT DURING HOT MONTHS - & Wasman, Mustafa (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
The present investigation was carried out to compare the impact of cinnamon and clove powders and their oil additives as anti-stressors on quails under heat stress which is one of the riskiest environmental conditions that influence poultry all over the world in general and Iraq in particular. For this purpose, 420 quails (5 weeks old) were chosen and randomly grouped into seven treatments with different treatments (T0: control (standard diet), T1: 2 g clove powder/kg diet, T2: 1 ml clove oil/kg diet, T3: 2 g cinnamon powder, T4: 1 ml cinnamon oil/kg diet, T5: 1 g clove powder+1 g cinnamon powder/kg diet, T6: 0.5 ml clove oil+0.5 ml cinnamon oil/kg diet) added to standard diet. The quails were fed with these diets for 17 weeks. The results indicated that adding clove, cinnamon, and their oils to quail diet under heat stress led to significantly (p<0.05) lower relative density of heat shock protein HSP40, HSP70, HSP90, the concentrations of (corticosterone hormone, MDA and CK oxidative stimulator enzymes in blood plasma) and heterophil-to-lymphocyte (H/L) ratio, however, the concentrations of antioxidant enzymes AOA, GPx, SOD and CAT in blood plasma were significantly (p<0.05) higher in all additive treatments compared with the control group. It was also seen that treatment with the oil additives resulted in higher improvement than the powder additives.